PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PERENCANAAN PEMBELAJARAN DI SEKOLAH DASAR - Nur Aini, Anandyah Nur Aini; Haris Novitasari, Rizka; Nadlir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The utilization of ICT in lesson planning in elementary schools or islamic elementary schools provides an opportunity for teachers to design learning activities that are more interactive, collaborative, and contextual. This research aims to find out how the utilization of ICT use in lesson planning, where lesson planning is an important thing to do first before the learning process in the classroom. The method used in this research is qualitative, the data for this research was collected using direct observation and interviews at SDN Wedoro Waru in addition to library or book study techniques. The result of this study shows that the utilization of ICT in lesson planning has many benefits to improve the quality of education by using online applications to create interactive and interesting lesson plans, using online learning platforms to provide more personalized and learner-centered learning opportunities. However, it cannot be denied that the utilization of ICT in the education sector has some barriers, such as the lack of ICT competence of teachers. The solutions that can be used to overcome these barriers are teachers need to get training and professional development to improve their ICT skills as well as some other solutions to overcome some other barriers. Keywords: Lesson Planning, Information and Communication Technology, The Utilization